The Malala Fund's Strategy to Fight For Women's Right to Get Education in Pakistan - Amannie, Nadya Sri Aisyah; Putri, Alfredha Shinta (Malikussaleh Social and Political Reviews, 2024)
The Right to Education for women is a part of human rights, where the right to education is considered essential for individuals to meet their educational needs and achieve their desired level of education. Women's right to education in Pakistan has become a significant issue due to various socio-economic and cultural barriers. This article examines the educational disparity between men and women in Pakistan, driven by social, cultural, and economic factors. Patriarchal cultural norms, poverty, and the lack of educational facilities are the main obstacles for women in accessing quality education. Furthermore, social stigma and traditional gender roles also limit their participation in education and social life. The Malala Fund, founded by Malala Yousafzai after the Taliban attack in 2012, has emerged as a leading force in advocating for women's right to education. The Malala Fund aims to reduce the gender gap in education by providing financial support, strengthening local programs, and raising global awareness about the importance of girls' education. Collaborations with UNESCO, NGOs, and the Pakistani government have laid the foundation for creating meaningful change for women, especially in rural areas with limited infrastructure. Although there has been progress in advocating for women's right to education, significant challenges remain, particularly related to patriarchal cultural norms, limited resources, and government policies that are not yet fully optimized. This research employs a qualitative descriptive model, with data collection through secondary sources or literature reviews from books, journals, news articles, and official websites.